Exploring the theological foundation of Corpo rate Social Responsibility in Islam, Christianity and Judaism for Strengthening Compliance and Reporting: An Eclectic Approach (Issues in Social and Environmental Accounting (ISEA), 2013)
Religion in the contemporary times has potentials from which conventional models and theories could leverage for public wellbeing. Considering the moral and ethical dimensions of corporate social responsibility (CSR), understanding this nebulous concept from the religious lenses could help strengthen CSR compliance and reporting in the industrial societies, where religions play direct and indirect role in corporate governance and people‘s lifestyle. This paper explores eclectic sources to provide answer to the questions: Does CSR have theological foundation in Islam Christianity and Judaism? Can religions strengthen CSR and fortify compliance and reporting? The authors sourced the required qualitative data from journal articles, Islamic jurisprudence, Judaic sources and Biblical texts as well as relevant online resources on the subject. The extractions from eclectic sources were subjected to content analysis from which conclusions on the two questions were established. The findings indicate that CSR has theological foundation in the three religions, and religious ethics and values could be potent drivers for strengthening CSR and reporting.